The effects of mathematical tasks on the seventh grade students' algebraic thinking and learning - Arabacı, Nil. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2018., 2018)
Algebra is one of the core branches of mathematics. However, many students fail in mathematics because they struggle with understanding algebraic concepts and procedures. Many scholars search for and propose effective ways of teaching and learning algebra to increase students’ mathematics achievement and understanding. In the light of such research, the aim of this study was to investigate effects of taskassisted instruction on the seventh grade students’ algebraic thinking and learning. This study was conducted in two of the seventh grade classes of a public middle school in Istanbul which taught by the same mathematics teacher. In one of the classes task-assisted instruction was applied for seven weeks while there was no intervention in the other class. The mathematics teacher taught in the same way in her regular mathematics course for both groups however the intervention took place in two-hour elective mathematics course of the experiment group. The test was administered before the study, just after the intervention and three months later the intervention to observe the retention. The tasks were developed to support three components of algebraic thinking: recognizing a pattern, writing algebraic expressions, setting up and solving equations. Students from the study group were grouped in threes or fours and one pre-service teacher was assigned for each group to manage the implementation of the tasks. The achievement test results showed that students in the study group performed significantly better than students in the control group. For post-achievement test U=124.000, p=.001 and for retention U=159.500, p=.013. Furthermore, video analysis revealed an improvement in at least two of three components of students’ algebraic thinking. Therefore, task-assisted instruction might be taught as one of the effective ways to support students’ algebraic thinking and learning.
Keywords: Algebra -- Study and teaching (Elementary)